Community of Seaweeds on Cemara Beach East Lombok - Intan Mushlihah; Lalu Japa; I Gde Mertha; Ahmad Raksun (Universitas Mataram, 2020)
Seaweeds (macroalgae) are a marine biological resource that have an important role in aquatic ecosystems and for society. The aim of this research was to determine community of seaweeds in Cemara Beach, East Lombok Regency.Data were collected at four observation points using a method of combinationof the line transect and quadrat. Seaweeds community data were analyzed using density parameters, important values, species diversity index, and species evenness index. The similarity percentage between transects was determined based on the Bray-Curtis cluster analysis using biodiversity program-version 2. In Cemara Beach there were 24 species of macroalgae which memberof 3 divisions, 11 orders and 15 families. Chlorophyta was a division with highest number of species. The number of species for Chlorophyta was 14 species, Rhodophyta division was 7 species, and Phaeophyta division 3 species. The species with highest density is Enteromorpha sp.,25.1 clumps/m2. Ulva lactuca is the species with the highest important value (72.69%). Diversity and evenness index in Cemara Beach seaweed species were 1,868 (medium category) and 0,699 (almost evenly distributed).The results of cluster analysis based on environmental parameters, species similarity and number of clumps of seaweed species, diversity index, and species evenness index indicate that seaweed in Cemara Beach can generally be divided into 2 groups.